A Simple Pre-concentration Method for the Determination of Nickel(II) in Urine Samples Using UV-Vis Spectrophotometry and Flame Atomic Absorption Spectrometry Techniques - Ahmed Fadhil Khudhair; Mouyed Khudhair Hassan; Hasan F. Alesary; Ahmed S. Abbas (Indonesian Journal of Chemistry, 2019)
The cloud point technique was effectively utilized for extraction and pre-concentration of nickel(II) in urine samples before measurement by UV-Vis spectrophotometer and AAS techniques. The metal response to a para-aminophenol (PAP) reagent in a non-ionic surfactant Triton X-114 medium was to form the Ni-PAP complex. The adopted concentration for PAP, concentration of Triton X-114, pH effect and water bath temperature, incubation time, salt effect, and interference effects were all optimized. The calibration curve was linear over the range of (0.0625–1.25) mg L–1 with a correlation coefficient r2 of 0.9682 for the UV-Vis spectrophotometer at a λmax of 629 nm. The limit of detection was 0.005 mg/L. The relative standard deviation for six replicates was 1.07%. This method was applied successfully to determine copper (II) concentrations in 44 urine samples of occupational worker samples as determined by UV-Vis spectrophotometry and FAAS techniques.